The Sexual Orientation of Panji : Cultural Construction in Intermediation - Seno Gumira Ajidarma (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2020)
The Panji love scenes from (1) Br. 126 manuscript in Jawi characters of Hikayat Panji Kuda Semirang, (2) Sastrawinata’s story book Panji Semirang published by Balai Pustaka, and (3) the comic book Panji Semirang by R. A. Kosasih, chronologically shows intermediation as a non-direct adaptation that represents the cultural construction that shifts the meaning, from a hidden signs of transgenderism to the domination of heterosexual orientation. The phenomena is connected with the fact that from early modern times (15th to 18th century) to second half of early modern period (17th to 18th century) in the region, there is the process where gender pluralism met the domination of mainstream religions and modern science, which marginalized and suppressed the former to the edge of normality. As transgender subculture still exists as an ideological struggle, the study of local genius should be done with a consciousness to contest the hegemonic discourse.